Подход к изучению изменения гидрологического режима и состояния экосистем водохранилищ в результате разработки месторождений песчано-гравийной смеси (Географический вестник=Geographical bulletin, 2017)
На основе системной методологии предложен подход к изучению изменения гидрологического режима и состояния экосистем водохранилищ в результате разработки месторождений песчано-гравийной смеси. Показан механизм формирования ямы размыва и посадки уровня в нижнем бьефе Камского гидроузла.The APPROACH To STUDYING CHANGE of the HYDROLOGICAL MODE And condition ecosystems of water basins as a result of development of deposits mix of sand and gravelOn the basis of system methodology the approach to studying change of a hydrological mode and condition ecosystems of water basins as a result of development of deposits mix of sand and gravel is offered. The mechanism of formation of a hole of washout and landing of a level in tail-water of the Кама hydrounit is shown.